Interstitial spinal-cord oedema in syringomyelia associated with Chiari type 1 malformations. Issue 10 (10th April 2008) - Akiyama, Y; Koyanagi, I; Yoshifuji, K; Murakami, T; Baba, T; Minamida, Y; Nonaka, T; Houkin, K
Abstract : Object: The pathophysiology of syringomyelia in Chiari type 1 malformations has not been clarified. Oedema-like spinal-cord swelling was recently reported in several pathological conditions, including Chiari type 1 malformations as a pre-syrinx state. However, the role of the pre-syrinx state in the development of syringomyelia is unknown. The purpose of this study is to investigate the parenchymal changes of the spinal cord in syringomyelia associated with Chiari type 1 malformations. Methods: Pre- and postoperative MRI findings in 14 patients who underwent foramen magnum decompression in our institute were reviewed. The analysis was focused on differences in visualisation of the syrinx between T1- and T2-weighted images and abnormal parenchymal signal changes. There were 6 men and 8 women, aged from 6 to 79 years. No patients showed hydrocephalus. Results: Twelve patients had large and expansive syrinx, whereas 2 patients showed small syrinx confined to the centre of the spinal cord. T2-weighted images displayed significantly larger intramedullary abnormal signal areas. Nine patients showed parenchymal hyperintensity areas around the enlarged central canal or base of the posterior white columns adjacent to the syringomyelic cavity. Such parenchymal hyperintensity areas markedly diminished with reduction of the syrinx after surgery and were considered to be interstitial oedema. Conclusions: From this study, the interstitial oedema of the spinal cord commonly accompanies syringomyelia with Chiari type 1 malformations. Accumulation of the extracellular fluid due to disturbed absorption mechanisms may play an important role in the pathophysiology of syringomyelia associated with Chiari type 1 malformations.